Investment analysis of plum brandy production – methodology approach - Hadelan, Lari (Applied Studies in Agribusiness and Commerce, 2008)
The major prerequisite of successful entrepreneurship venture is quality of decision-making process. Decision in investment is the most important financial decision. It is a part of both long-term business planning process and strategic business definition. Using available investment appraisal methods, entrepreneur should make positive or negative investment decision. Within the development of the economic theory and the practice many of methods made decision-making process rational and gave the scientific and practical base for successful project evaluation.